A tele-operated mobile ultrasound scanner using a light-weight robot. - Delgorge, C.
This paper presents a new tele-operated robotic chain for real-time ultrasound image acquisition and medical diagnosis. This system has been developed in the frame of the Mobile Tele-Echography Using an Ultralight Robot European Project. A light-weight six degrees-of-freedom serial robot, with a remote center of motion, has been specially designed for this application. It holds and moves a real probe on a distant patient according to the expert gesture and permits an image acquisition using a standard ultrasound device. The combination of mechanical structure choice for the robot and dedicated control law, particularly nearby the singular configuration allows a good path following and a robotized gesture accuracy. The choice of compression techniques for image transmission enables a compromise between flow and quality. These combined approaches, for robotics and image processing, enable the medical specialist to better control the remote ultrasound probe holder system and to receive stable and good quality ultrasound images to make a diagnosis via any type of communication link from terrestrial to satellite. Clinical tests have been performed since April 2003. They used both satellite or Integrated Services Digital Network lines with a theoretical bandwidth of 384 Kb/s. They showed the tele-echography system helped to identify 66% of lesions and 83% of symptomatic pathologies.
Keywords: Ultralight Robot European Project; Compression techniques; Control law; Image compression and filtering; Image processing; Image transmission; Integrated services digital network lines; Light-weight robot; Mechanical structure; Medical diagnosis; Medical robotics; Mobile communication; Mobile tele-echography.; Real-time ultrasound image acquisition; Remote center of motion; Remote ultrasound probe holder system control; Satellite; Tele-operated mobile ultrasound scanner